Performance over Strategy: A Myth of Denial in Sponsorship among Football Clubs in Ghana - Frank Appiah Kusi, (The Bioscan, 2026)
This article interrogates the prevailing assumption among Ghanaian football club owners and managers that on-field performance is the primary driver of sponsorship acquisition. Drawing on comparative insights and sponsorship theory, it argues that the overemphasis on performance masks a deeper strategic vacuum.